Infrastructural subjectivities and subjective infrastructures land, time, value, and the effective work of infrastructure in Dubai and the farm, Western Cape, South Africa - Van der Westhuizen, Nicola (Stellenbosch : Stellenbosch University, 2026)
Thesis (DPhil)--Stellenbosch University, 2025.